Exchange and Investment Approach as a Framework for Analysis of the Organizational Commitment of Teachers of Privates Schools of Morang, Nepal - Rai, Arjun; Rai, Chandra Kumar (Dristikon: A Multidisciplinary Journal, 2020)
This study investigates the effect of monthly pay, the number of dependents of the teachers, age, and tenure year on the organizational commitment of the teachers working in the private schools of Morang. The population in this study includes all teachers working in the private schools of Morang district. This study used a pre-tested instrument to collect the data. This study employed multiple regression analysis as an analytical tool to test the hypothesis of the research. Statistical Package for Social Science (SPSS), version 25, was used for the data analysis. The findings of the study- monthly pay, the number of dependents in the family of the teachers, and age had a significant positive impact on the organizational commitment of the teachers, but and tenure year had a significant negative effect on the organizational commitment. The originality of this study: this study shows (1) the effects of monthly payments, the number of people dependent on the job holder, age, and tenure period on the organizational commitment in the Nepalese setting. (2) Location and the population of the study are unique (no previous researches were conducted to examine the relations between the dependent and independent variables used in this study; the target population of the study- the teachers working in the private schools in Morang.